Evaluation of a Commercially Available Organic Acid Product During Feed Withdrawal and its Relation to Carcass Shrink in Commercial Turkeys - Pixley, C.; Barton, J.; Vicente, J.L.; Wolfenden, A.D.; Hargis, B.M.; Tellez, G. (International Journal of Poultry Science, 2010)
The transport of live animals has important economic and welfare implications. A commercially-available organic acid product (Optimizer™) was added to the drinking water of commercial hen turkeys during preslaughter Feed Withdrawal (FW) in two trials. In trial 1, a total of 60 trailers from treated (OA) or control non-treated turkey houses were evaluated. Turkey farmers initiated water treatment on the day before pick up (8-12 h treatment according to label directions). Investigators recorded trailer numbers as they were loaded out of each house to confirm which trailers contained treated birds vs. control non-treated birds. Individual trailer weights were recorded upon arrival to the processing plant and again immediately prior to live hang. A significant reduction in rate of weight loss during holding at the processing plant was observed in the treated turkeys (719 g/min per OA treated trailer vs. 845 g/min per control trailer). In trial 2, two commercial market age turkey houses were selected and in each house, 400 birds were weighed and recorded as a representative sampling. The treated house received OA administered according to manufacturer’s directions continuously for 19 h. At the end of this time, 400 birds were weighed and recorded as a representative sampling. A significant (p